Overcoming communication barriers in a multicultural radiography setting - Cherise Janse van Vuuren; Barbara van Dyk; Padidi L. Mokoena (AOSIS, 2021)
Background: Effective communication between the patients and radiographers can be a daunting task in a multicultural, multilingual environment. With 11 official languages, South Africans experience language barriers amongst themselves, which pose unique communication challenges on a daily basis. It is thus important to explore how radiographers overcome such challenges to provide an effective service to their patients. Aim: The aim of this study was to explore and describe the experiences of radiographers in Gauteng province in communicating with patients in a multilingual, multicultural healthcare setting and make recommendations towards overcoming such barriers. Setting: The focus group discussions were conducted in English and at a private location that was convenient for the participants in Gauteng. Method: The study employed a qualitative phenomenological approach using focus group interviews (FGIs) to solicit the experiences of participants and gain an in-depth understanding of the phenomenon. Results: The findings showed that patient-radiographer cross-cultural communication is ineffective whilst language barriers are encountered daily. Participants subsequently offered a number of recommendations to enhance communication with patients from different cultural and linguistic backgrounds. These included workshops or short courses to improve language skills, posters to allow for non-verbal communication, the use of professional interpreters or mobile translation technology, employment of a diverse workforce and a focus on cultural sensitivity and learning an additional language at tertiary level. Conclusion: Although a variety of communication strategies are available, the most appropriate combination should be explored for individual radiology practices in order to serve their respective diverse patient base. Recommendations that emanated from this study can, therefore, be used as a guide to radiology practices to facilitate effective patient-radiographer communication.